Black resistance in the Americas - Dunkley, Daive A. 1973-; Shonekan, Stephanie (Routledge, Taylor & Francis Group, 2019)
All across the US in the last few years, there has been a resurgence of Black protest against structural racism and other forms of racial injustice. Black Resistance in the Americas draws attention to this renewed energy and how this theme of resistance intersects with other communities of Black people around the world. This edited collection examines in depth stories of resistance against slavery, narratives of resistance in African American, Afro-Caribbean, and Afro-Latin American Literature, resistance in politics, education, religion, music, dance, and film, exploring a range of new perspectives from established and emerging researchers on Black communities. The essays in this pivotal book discuss some of the mechanisms that Black communities have used to resist bondage, domination, disempowerment, inequality, and injustices resulting from their encounters with the West, from colonization to forced migration
Keywords: Blacks / Political activity / America; Blacks / America / Intellectual life; Blacks / America / Social life and customs; Blacks / America / Social conditions; Racism / America